The debris impact response of the space shuttle wing. (9th January 2009) - Sanders, Jessica; Gwinn, Kenneth W.; Khraishi, Tariq
This paper serves as an investigation into the response of the NASA space shuttle wing in the event of a debris impact during launch. The explicit finite element method is used to model the leading edge of the shuttle wing and the event of impact with a piece of a material from the shuttle's external tank. The results will be utilised by the Impact Penetration Sensor System (IPSS) to help characterise the signal received by the system in the event of an actual impact. Numerical results are validated by experiments done at the Southwest Research Institute (SwRI).